The evolution of compounding research in semantics: A decade of scientometric evidence (2014â€”2024) - Danang Satria Nugraha; I Kadek Purnawan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Although compounding has been widely examined within linguistic research, a systematic overview of its semantic research landscape remains underdeveloped. This study addresses this gap by offering a scientometric mapping of trends and thematic orientations in semantic research on compounding. Drawing on a corpus of 376 publications indexed in the Scopus database between 2014 and 2024, the analysis adopts a quantitative approach and employs VOSviewer to examine publication patterns, thematic structures, and research trajectories. The findings point to a steadily expanding field, with an average annual increase of approximately three publications and an overall growth of 187.5% across the eleven-year period. Reading and Writing, Cognition, and Mental Lexicon emerge as the most prominent publication venues. Thematic analysis identified three principal clusters: (a) â€œCompounding Formation and Descriptionâ€ (40.71%), encompassing terms such as â€œaffixation,â€ â€œmorphology,â€ â€œneologism,â€ and â€œword formation process,â€ (b) â€œCognitive and Developmental Aspects of Compoundingâ€ (20.09%), characterized by keywords including â€œmorphological awareness,â€ â€œcomprehension,â€ â€œdevelopment,â€ and â€œstudent.â€, and (c) â€œSemantic Interpretation and Theoretical Frameworksâ€ (29.20%), which includes terms such as â€œword meaning,â€ â€œsemantic composition,â€ â€œsyntax,â€ and â€œtheory.â€ Taken together, these findings offer insights into the current state and trajectory of compounding research in the light of semantics, highlighting key themes within the current patterns of advancement.